IDENTIFIKASI KEANEKARAGAMAN SERANGGA PADA PERKEBUNAN JERUK PAMELO DI DESA BANDAR, KECAMATAN SUKOMORO, KABUPATEN MAGETAN SEBAGAI BAHAN PENYUSUNAN LKS POKOK BAHASAN KEANEKARAGAMAN HAYATI - Kartika Dwi Ermawati; Sri Utami (Jurnal Pendidikan, 2013)
The presence of insect pests often makes citrus fruit is damaged, rotten, and finally yellow, resulting in losses among farmers. But not only harmful insects are contained in a plantation area. Sometimes insects also benefit farmers, such as insects that act as natural predators for insect pests. This study aims to determine the kinds of insects and determine the identification and classification of insects found in plantation area in the village of Bandar pamelo, Sukomoro, Magetan. This research is descriptive qualitative which leads to a detailed description of the data. Data collection was done by direct observation and with the help of Net Flay and traps with methyl eugenol. The results showed that there are insects that act as pests or insects that act as predators who are on the plantation pamelo. Including pest insects are family Tephritidae, the family Acrididae, Tettigoniidae family, Papilionidae family, family Pyrrhocoridae, family Coreidae , family Flatidae. While insects act as predators that Aeshnidae family, family Mantidae, family Formicidae, family Coccinellidae. LKS is a book that contains a summary of the discussion at the same set of questions. Through the use of worksheets teachers, not only in supporting books that are universal, but the teacher can adjust to the conditions and situations that occur in students' learning and the school in question.